Institutional Trends in Opioid Prescribing and Utilization after Primary Cleft Lip and Palate Repair. Issue 4 (29th July 2022) - Sacks, Gina N.; Makar, Katelyn G.; Harbaugh, Calista M.; Cooper, Karen A.; Vercler, Christian J.; Kasten, Steven J.; Buchman, Steven R.; Waljee, Jennifer F.
Abstract : Background: Outpatient prescriptions for postoperative pain play an important role in the opioid epidemic. Prescribing guidelines are an effective target for intervention but require procedure-specific data to be successful. The aim of this study was to examine opioid prescribing patterns and pain control after primary cleft lip and palate repair at a large academic center. Methods: Children undergoing cleft lip and palate repair from April of 2018 to July of 2019 were included in a prospective cohort study. Data on discharge prescriptions, refills, and emergency room visits were obtained from the medical record. Caregivers were surveyed 7 to 21 days after surgery regarding pain control, opioid use, education exposure, storage, and disposal. Chi-square tests and one-way analysis of variance were used to examine predictors of pain control, opioid consumption, safe storage, and disposal. Results: After screening, 59 children were included in the study. Patients were 55.8 percent male with a median age of 12 months (interquartile range, 5 to 15). Ninety percent of patients received an opioid prescription at discharge with a mean quantity of 10 doses (interquartile range, 5 to 15). Ninety-seven percent of caregivers used adjunct medication. Opioids were given for a median of 3 days (interquartile range, 2 to 6.5). Seventy-six percent of caregivers gave less opioid than prescribed. There was no association between pain control and opioid quantity ( p = 0.68). Twenty-four percent of caregivers used locked storage. Thirty-four percent of respondents with leftover medication reported disposal. Conclusions: Opioids are often overprescribed after cleft lip and palate repair. Providers should consider limiting prescriptions to a 3-day supply to help reduce the quantity of opioids available in the community.